Nocardioides vastitatis sp. nov., isolated from Taklamakan desert soil. Issue 1 (18th September 2019) - Liu, Shao-Wei; Xue, Chun-Mei; Li, Fei-Na; Sun, Cheng-Hang
Abstract : A Gram-stain-positive, aerobic, non-motile, rod-shaped actinobacterium, designated strain 21Sc5-5 T, was isolated from a soil sample collected in the Taklamakan desert in Xinjiang Uygur Autonomous Region, PR China and investigated by using a polyphasic approach. Strain 21Sc5-5 T grew at 10–37 °C (optimum, 28–30 °C), pH 6.0–9.0 (optimum, pH 7.0) and in the presence of 0–3 % (w/v) NaCl (optimum, 0 %). Phylogenetic analysis based on 16S rRNA gene sequences suggested that strain 21Sc5-5 T formed a distinct lineage within the genus Nocardioides and had the highest similarity to Nocardioides albidus THG-S11.7 T (97.30 %), followed by Nocardioides kongjuensis A2-4 T (97.22 %), Nocardioides nitrophenolicus NSP 41 T (97.15 %) and Nocardioides caeni MN8 T (97.15 %). The results of chemotaxonomic analyses showed that the isolate possessed ll -diaminopimelic acid as the diagnostic diamino acid of the peptidoglycan and MK-8(H4 ) as the predominant menaquinone. The polar lipids comprised diphosphatidylglycerol, phosphatidylglycerol, phosphatidylinositol, an unidentified phospholipid and three unidentified lipids. The major fatty acids were iso-C16 : 0 and 10-methyl C18 : 0 . The genome length of strain 21Sc5-5 T was 4.67 Mb containing 372 contigs and with a DNA G+C content of 70.4 mol%. On the basis of data from phylogenetic, phenotypic and chemotaxonomic analyses, strain 21Sc5-5 T represents a novel species of the genus Nocardioides, for which the name Nocardioides vastitatis sp. nov. is proposed. The type strain is 21Sc5-5 T (=JCM 33365 T =CGMCC 4.7608 T ).